A IMPORTÂNCIA DA SISTEMATIZAÇÃO DO ATENDIMENTO DE CRISES HIPOGLICÊMICAS EM AMBULATÓRIO (REMUNOM, 2025)
Hypoglycemia is one of the most common reasons for seeking outpatient care, or even emergency room care. It is known that these crises are caused by several factors, such as excessive physical exercise, lack of nutrition, incorrect use of insulin and diabetes medications, and even moments of anxiety. The methodology chosen was a systematic review, carried out based on the study of references already analyzed and ratified by written and electronic means. The objective was to verify the known forms of management of hypoglycemia crises, discussing the resolution and functionality of each one of them. A patient in an episode of hypoglycemia must be well guided by any professional who is going to provide first aid to this individual. Therefore, it is necessary that outpatient care be systematized, so that everyone can receive the correct diagnosis and the ideal treatment for each situation.KEYWORDS: Health. Hypoglycemia. Syncope. Glycemic Control